A near-infrared probe for detecting and interposing amyloid beta oligomerization in early Alzheimer's disease - Quan, Li; Moreno-González, Inés; Xie, Zhigang; Gámez, Nazaret; Vegas-Gómez, Laura; Song, Qinyong; Gu, Jianhua; Lin, Wenhai; Gómez Gutiérrez, Rubén; Wu, Tianfu (Wiley, 2023)
Background The misfolding and deposition of amyloid beta (Aβ) in human brain is the main hallmark of Alzheimer's disease (AD) pathology. One of the drivers of Alzheimer´s pathogenesis is the production of soluble oligomeric Aβ, which could potentially serve as a biomarker of AD. Methods Given that the diphenylalanine (FF) at the C-terminus of Aβ fragments plays a key role in inducing the AD pathology, based on the hydrophobic structure of FF, we synthesized a near-infrared BF2-dipyrrolmethane fluorescent imaging probe (NB) to detect both soluble and insoluble Aβ. Results We found that NB not only binds Aβ, particularly oligomeric Aβ, but also interposes self-assembly of Aβ through π-π interaction between NB and FF. Conclusion This work holds great promise in the early detection of AD and may also provide an innovative approach to decelerate and even halt AD onset and progression.
https://openpolicyfinder.jisc.ac.uk/id/publication/10547
Keywords: Alzheimer, Enfermedad de; Amiloide; Aminoácidos; Alzheimer's disease; BODIPY; Amyloid beta oligomer; Diphenylalanine; Near-infrared probe